A transcriptional biosensor reveals mechanisms of α-ketoglutarate signaling to chromatin - Alex C. Sternisha; Haocheng Li; Kumar Gajendra; Yi Xiao; Xin Zhao; Jeffrey I. Traylor; Lei Guo; Ji Hyung Jun; Morgan Fleishman; Tracey Shipman; Vinesh T. Puliyappadamba; Pranita Kaphle; et al. (Science, 2026)
The metabolite α-ketoglutarate (αKG) is required for chromatin demethylation, but mechanisms that control αKG abundance in the nucleus are poorly defined. We designed a biosensor to monitor this metabolite pool in human cells using an αKG-responsive cyanobacterial transcription factor, NtcA, and used it to identify genes that regulate αKG in the nucleus. We defined an interorganelle pathway in which sequential mitochondrial activities of glutamic-pyruvic transaminase 2 (GPT2) and the SLC25A11 transporter supply nuclear αKG. In a mouse model of GPT2 deficiency, an inborn error of metabolism, Gpt2 loss caused histone hypermethylation in the brain and dysregulated neurodevelopmental genes. Restoring αKG counteracted these changes and promoted mouse fitness. Our work provides a tool to directly monitor nuclear αKG and reveals nuclear αKG depletion as a key pathogenic mechanism underlying GPT2 deficiency.